Tea flavour : delivery and perception - Wright, Jonathan P. (2007)
A novel method was developed, enabling volatile release from mugs of freshly prepared, hot black tea infusions to be monitored online using atmospheric pressure chemical ionization-mass spectrometry (APCI-MS). Given the number of volatile compounds contributing to the aroma of black tea infusions, and the one dimensional nature of the APCI-MS technique, it was necessary to determine which ions present on APCI-MS spectra corresponded to which volatile compounds present in tea headspace.